PEMBELAJARAN BERBASIS BLENDED LEARNING DI SEKOLAH MENENGAH ATAS NEGERI 2 SOPPENG SULAWESI SELATAN - Suci Cahyani; Syamsurijal Basri; Sumarlin Mus (KLASIKAL : JOURNAL OF EDUCATION, LANGUAGE TEACHING AND SCIENCE, 2022)
This study aims to determine the portrait of the implementation of Blended Learning-Based Learning learning consisting of planning, implementing, and evaluating knowledge. This research approach is qualitative with a type of description research—data collection techniques are in the form of interviews, observations, and documentation. The data analysis technique uses miles and Huberman models. They are checking the validity of the data using triangulation techniques. The results showed that: Learning planning There is no specific policy issued by schools regarding blended learning-based learning, preparation of human style resources in the form of In House Training (IHT) training to teacher teachers regarding procedures for using the Learning Management System called Google Classroom, Implementation of learning, teachers choosing methods and media to be used, the level of student activity in the blended learning process is greatly influenced by available networks, online learning strategies that are taking material from the internet, media used when learning blended laptops and cellphones, learning applications used by Google Classroom, Zoom Meeting, Google Meet, WhatsApp, and Telegram. Evaluation of realizing using a different learning system during online learning with face-to-face learning, the form of assessment given by the teacher online is in the form of quizzes and online tests through learning applications, while when offline, the teacher provides a direct evaluation in the form of hardcopy of questions to students.